The relation of the forest to civilization - Dial, George Henry (My University, 1896)
Introduction: Every one enjoys the foliage of nature as it is presented, in all its beauty fragrance and grandeur, on every side. The field that is covered with shade trees and bedecked with flowers and shrubbery arranged in the most magnificent manner attracts the eye of all who pass by. It gives an impulse to their activities; it furnishes inspirations, enlivening them in their work.
Citation: Dial, George Henry. The relation of the forest to civilization. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Nature; Flowers; Shrubbery; Theses; Manuscripts (documents)